Pelatihan Pembuatan Keripik Pakcoy pada Kelompok Wanita Tani (KWT) di Dusun Kunden, Godean, Yogyakarta - Hidayah Risalatus Siyam; Ridha Hana Islama; Alfaani Ulfy Naashiroh; Arum Dwi Mahatfi; Tuminah Tuminah; Ignatia Esti Sumarah (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
The implementation of the Leadership Project course in the Teacher Professional Education Program (PPG) aims to train students to implement service learning through real activities in the community. This article explains This article explains the training activities for making pakchoy chips with the Women Farmers Group (KWT) in Dusun Kunden, Godean, Yogyakarta as a form of community service. The training is a means to improve the creativity and skills of KWT mothers in processing agricultural products into products of economic value. The method used in this study is qualitative research with a narrative approach. Community service is carried out through several stages, namely preparation, implementation, and evaluation. The results of the activity show that training participants are able to understand the process of making pakchoy chips and see the potential of this product as a business opportunity. This training is expected to equip KWT mothers to practice independence and entrepreneurship to make pakchoy chips with various flavors.